الفساد والنمو الاقتصادي: أدلة تجريبية لعينة من دول الشرق الأوسط وشمال إفريقيا خلال الفترة 1996-2019 - نصيب, حفيزة; جوادي, عصام; دراجي, وليد (جامعة الوادي - University of Eloued, 2021)
الهدف من هذا البحث هو دراسة أثر الفساد على النمو الاقتصادي لمجموعة من دول المينا خلال الفترة 1996-2019، باستعمال نماذج التكامل المشترك لبيانات البانيل ، أظهرت النتائج وجود أثر إيجابي معنوية للفساد والنمو الاقتصادي في دول المينا، كما اظهرت النتائج أيضا تأثيرات ايجابية معنوية لكل من مخزون رأس المال البشري، الاستهلاك الحكومي ووفرة الموارد الطبيعية، الأمر الذي يعني أن هذه العوامل هي أهم محددات النمو الاقتصادي في دول منطقة الشرق الأوسط وشمال إفريقيا. Abstract: This research aims to examining the impact of corruption on economic growth in simple of MENA countries during the period 1996-2019, by using econometrics co-integration models of Panel data. The results showed a significant positive impact of corruption and economic growth in the MENA countries. The results also showed significant positive effects for human capital accumulation, government consumption and natural resources abundance, which means that these factors are the most important determinants of economic growth in Middle East and North Africa countries.
Corruption and Economic Growth: Empirical Evidence from Middle East and North Africa during the period 1996-2019
Keywords: نمو اقتصادي ; فساد ; هبات طبيعية ; نماذج تكامل مشترك; Economic growth ; corruption ; natural dotation ; co-integration models